An Assessment of the Role of Women Group in Women Political Participation, and Economic Development in Nigeria - Orisadare, Monica Adele (Frontiers in Sociology, 2019)
The exclusion of women in politics has been identified in recent times as one of the major setback for economic development. Women’s groups a strong pillar for grassroots politics; and a driver of more women participation in politics at the grassroots still faces a lot of challenges making it difficult for them to harness available opportunities for economic development. Thus, the opportunity therein for more women participation in politics and women empowerment is yet to be exploited by the women’s groups in Nigeria. This present study assesses the role of women’s groups in politics, identifies their challenges and also explores its implication for economic development in Osun state, Nigeria. The study was carried out using primary data from forum and dialogues with6 women’s groups consisting of an average of thirty (30) members from ten (10) local government areas (LGAs) in Osun state, Nigeria. In addition explorative methods using existing literature were also employed. Findings from the study indicate that women’s groups do not have political agenda; their goals most times do not align with any political agenda, although their members accept appointments, and also enjoys government patronage. There was also an indication that there exist a high illiteracy rate among the members of the women’s group and most of them are not aware of existing National nor International gender equality laws or affirmative action, thus, it is difficult to participate in politics and contributes their voices to political issues. The study concludes that the present role played by the women groups at the grassroots level may not be adequate to encourage more women’s participation in politics and influence economic development, thus there is need to step up their activities to embrace political issues if more women are to participate and be relevant in politics. The study therefore suggests that more empowerment programs especially in area of decision making and participation in politics be targeted at women groups at the grassroots levels by the governments and all stakeholders as a matter of priority.